Low temperature synthesis and NOx sensing properties of nanostructured Al-doped ZnO - Navale, S. C.; Ravi, V.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2007)
Although ZnO is studied intensively as a sensing material, there are limited reports available on aluminum-doped ZnO (AZO) as a NO, sensor. This paper reports selective NO, sensing characteristics of M-doped ZnO synthesized in the form of porous pellets sintered at 350 degrees C. The salient feature of our experimental results is that our sensor can detect small concentrations of NO, at lower operating temperature. It is also observed that as compared to gases such as SOx HCl, LPG, H2S, H-2, ammonia, alcohol and acetone it selectively detects NOx due to Al-doping. The amount of Al in ZnO during synthesis is varied between 1 and 10 wt%. Our sensor senses NO, concentration as low as 20ppm at 100 degrees C with a %response of 11 and a %response of 740 at 300 degrees C for 1 wt% Al. Of all the compositions with Al-doping, I wt% is found to give best results. Sensing experiments carried out at 350 C, however. do not show any significant improvement in the gas sensing properties. The phase contents and lattice parameters were determined by XRD and the average particle size was obtained using Scherrer formula. A probable mechanism for sensing NO, involving oxygen ion adsorption and desorption on the surface of sensor has been suggested. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: aluminum doping; nanomaterial; NOx; Sensor; ZnO